Culture and corporate governance - Aluchna, Maria; Postuła, Igor (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Corporate governance refers to the structure of mechanisms and institutions which monitor and supervise companies. This structure is determined by the interplay of political, social and cultural factors which impact the institutional framework for companies’ functioning. The systemic approach studies the links and mutual influence of various determinants upon the shape of the corporate governance structure. The article adds to this literature focusing on the impact of cultural determinants on the functioning governance mechanisms and institutions. The article is of theoretical character and it aims to propose a conceptual model of relations between culture and corporate governance aspects.